A toolset of image processing algorithms for forensic document examination - Yan, Solihin (2009)
One of the tasks of a forensic document examiner is to analyse the authorship of a handwritten document. The purpose of such analysis is to determine whether a document has been forged (forgery identification), to determine whether an author has tried to disguise his handwriting (disguised writing identification), or to identify the author of a document (writer identification).